THE DEVELOPMENT OF ALTERNATIVE FEED AND PROBIOTIC APPLICATION ON CATFISH INSTRUMENTS IN JEMIRAHAN VILLAGES - nasrullah bai arifin (Journal of Innovation and Applied Technology, 2017)
African catfish (Clarias gariepinus) is widely cultured freshwater species in Indonesia as well as in Jemirahan, Sidoarjo. Two major problems of catfish culture in this area is low survival rate and low margin due to high cost in feed utilization. The purpose of this activity was to evaluate the application of probiotic and alternative feed in catfish culture. Fish fry of 7-9 cm in size was cultivated for 90 days in rearing activity. All tanks were treated by probiotic during one cycle of culture. Probiotic was directly given to the water and administered by feed. The results showed that survival rates obtained during cultured periods was 92%. Meanwhile, feed conversion ratio value was 1.5. It can be concluded that probiotic application was able to improve the survival rate and the use of alternative feed was able to replace commercial feed.